Clinical research regulation in India-history, development, initiatives, challenges and controversies: Still long way to go - Mohammed Imran; Abul K Najmi; Mohammad F Rashid; Shams Tabrez; Mushtaq A Shah (Wolters Kluwer Medknow Publications, 2013)
The Central Drugs Standard Control Organisation and its chairman Drug Controller general of India are bequeathed to protect the citizens from the marketing of unsafe medication. The startling findings, of the 59 th report of the Parliamentary Standing Committee on Health and Family Welfare, have uncovered the lax standards followed by the regulatory authorities in India. The growing clinical research after the product patents rights for the pharmaceutical industries as per the trade related aspects of intellectual property rights agreement and adverse drug reaction monitoring of the marketed drugs have raised many ethical and regulatory issues regarding the promotion of new drugs in Indian markets. Many controversial group of medicines; unauthorised and irrational FDCs not relevant to India's medical needs, are available which are not sold in any of the countries with matured regulatory bodies. It becomes vital to understand the history, growth and evolution of the regulatory aspects of drugs which are handled by multiple Ministries and Departments of the Government of India. Although amendment to Schedule Y, registration of Contract Research Organisations, registration of Clinical Trials, Speeding up review process, Pharmacovigilance (PhV) programme for India and Inspection of clinical trial sites have been started by the various regulatory agencies. However due to casual approach in marketing approval for sale of the drugs, the unethical steps taken by some pharmaceutical companies and medical practitioners has reiterated the need to get appropriate understanding of present regulation of drugs and clinical research especially regarding the practical rules and regulations.